2003
DOI: 10.1002/job.184
|View full text |Cite
|
Sign up to set email alerts
|

Does job insecurity lead to impaired well‐being or vice versa? Estimation of cross‐lagged effects using latent variable modelling

Abstract: SummaryAlthough research suggests that job insecurity is associated with impaired employee wellbeing, there is insufficient empirical evidence to draw any causal inferences since most studies are cross-sectional and thus do not control for previous levels of health symptoms. We used longitudinal questionnaire data to investigate the direction of the relationship between job insecurity and health complaints. After controlling for prior levels of mental and physical health complaints and five other variables tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
194
0
17

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(224 citation statements)
references
References 55 publications
8
194
0
17
Order By: Relevance
“…This is consistent with past studies showing that job insecurity explains for substantial variance in job stress measures. Many previous studies have shown that job insecurity related to job attitudes such as satisfaction (Probst & Brubaker, 2001), organizational attitudes such as organizational commitment and trust, and psychological and physical well-being outcomes (Hellgren & Sverke, 2003;Kivimaki, Vahtera, Pentti, & Ferrie, 2000). A few studies have identified additional work-related behaviors such as increased job search behavior (Adkins, Werbel, & Farh, 2001;Reisel & Banai, 2002) or safety (Probst & Brubaker, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with past studies showing that job insecurity explains for substantial variance in job stress measures. Many previous studies have shown that job insecurity related to job attitudes such as satisfaction (Probst & Brubaker, 2001), organizational attitudes such as organizational commitment and trust, and psychological and physical well-being outcomes (Hellgren & Sverke, 2003;Kivimaki, Vahtera, Pentti, & Ferrie, 2000). A few studies have identified additional work-related behaviors such as increased job search behavior (Adkins, Werbel, & Farh, 2001;Reisel & Banai, 2002) or safety (Probst & Brubaker, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite, many studies have done in examining the impact of job insecurity in workplace (Probst & Brubaker 2001;Hellgren & Sverke, 2003;Kivimaki, Vahtera, Pentti, & Ferrie, 2000), but the study that verified the role of religious coping as moderator variable is few in current literatures. Whether religious coping may modifies the impact of job insecurity on job stress remains an open question and unclear, especially in Javanese culture sample.…”
Section: National Institute Of Occupational Safety and Health (Niosh)mentioning
confidence: 99%
“…It should be recognized that reversed effects involving other work-related stressors/outcomes have also been tested in the literature. For example, the reciprocal relationships involving job insecurity (69,87), effort-reward imbalance (88), or constructs involved in the work motivational process of the Job Demands-Resources model (eg, work engagement ↔ job resources) have also been previously explored (54,55,68). These were considered beyond the scope of the current review.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Cross-sectional studies have established that job insecurity is associated with negative consequences. However, only a few studies, mainly focusing on health outcomes, such as Hellgren, and Sverke (2003) or Ibrahim, Smith, and Muntaner (2009), have investigated the directionality of job insecurity and its outcomes. More research is needed on job insecurity and its possible consequences, and the directionality of these relations, in order to increase our knowledge about the potential outcomes that follow job insecurity as well as the potential durations of its effects.…”
Section: The Uncertainties In Today's Working Lifementioning
confidence: 99%